P-86 The admiral nurse project: proactive approaches to effective dementia support in a UK hospice. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Mountford, Wendy; Read, Sue
Abstract : Background: Dementia is a progressive neurodegenerative disease. There are some treatments that will alleviate some symptoms but dementia is not curable and is a terminal illness. It is estimated 850 000 people are living in the UK with a diagnosis of dementia and 670 000 are people acting as primary carer for a loved one with dementia (Alzheimer's Society, 2015). UK hospices are being encouraged to engage in the agenda of dementia care for people who are palliative or end of life. Aim: To present the independent, interim evaluation of a service for people with dementia in a hospice setting. Methods: A qualitative evaluation approach was used within a participatory action research framework, incorporating several phases across the general participatory action research (PAR) framework (Brydon-Miller, 2004). This cyclical process was adopted, alternating continuously between enquiry and action, and between practice and innovative thinking (Hart & Bond, 1995). This alternating process enables implementation of change and ultimately generation of theory (Greenwood, 1994). Six focus groups (n=43) and a survey were conducted to formally evaluate the implementation of the dedicated support within a specialist hospice in the UK. Results: The PAR approach was a useful framework to promote ongoing change within a dynamic hospice environment. Interim results found that the Admiral Nurses project provides a useful template to inform change within a hospice environment; demonstrate the breadth of impact of the service from a patient, family and professional perspective; and highlight how such an initiative can be the catalyst for effective strategic and operational change. Conclusion: The numbers of people with dementia is increasing world-wide, and issues around effective and specialist support are challenging. Expanding the hospice role to include patients with dementia requires investment in dementia specialist nurses to complement existing hospice expertise.